The Impact of Strategic Renewal on Startup Performance: The Role of Digital Transformation and Market Pressure in SaaS-Based Startups in Jakarta and Surabaya - Robertus Adi Nugroho; Bernardus Aris Ferdinan; Maria Indah Lestari Sepungan (Petra International Journal of Business Studies, 2025)
The performance of a newly formed business is critical. This is especially true for organizations that are in fast-changing and intensely competitive markets. This study examines business performance and strategic renewal with particular emphasis on digital transformation as a mediator and market pressure as a moderator. Grounded in the Dynamic Capability Theory, the study sampled 181 Software as a Service (SaaS) startups in Jakarta and Surabaya, and the data were analyzed using PLS-SEM. The study found that strategic renewal and digital transformation (β = 0.647; p < 0.001) and organizational performance (β = 0.874; p < 0.001) are all significantly and positively correlated. The lack of evidence for the impact of strategic renewal on performance (β = 0.016; p = 0.753) suggests that there is no relationship, which is indicative of full mediation, with the implication that digital transformation is a full mediator. In addition, market pressure positively moderates the relationship between digital transformation and performance (β = 0.120; p = 0.017), underscoring the importance of industry competition. The study also contributes to dynamic capability theory by demonstrating the relationships among strategic renewal, digital transformation, and performance. The main practical implications from the research is that strategic plans should be combined with agile responsive digital market strategy plans.